The role of accreditation in 21st century health professions education: report of an International Consensus Group - Frank, Jason R; Taber, Sarah; van Zanten, Marta; Scheele, Fedde; Blouin, Danielle (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background Accreditation is considered an essential ingredient for an effective system of health professions education (HPE) globally. While accreditation systems exist in various forms worldwide, there has been little written about the contemporary enterprise of accreditation and even less about its role in improving health care outcomes. We set out to 1) identify a global, contemporary definition of accreditation in the health professions, 2) describe the relationship of educational accreditation to health care outcomes, 3) identify important questions and recurring issues in twenty-first century HPE accreditation, and 4) propose a framework of essential ingredients in present-day HPE accreditation. Methods We identified health professions accreditation leaders via a literature search and a Google search of HPE institutions, as well as by accessing the networks of other leaders. These leaders were invited to join an international consensus consortium to advance the scholarship and thinking about HPE accreditation. We describe the consensus findings from the International Health Professions Accreditation Outcomes Consortium (IHPAOC). Results We define accreditation as the process of formal evaluation of an educational program, institution, or system against defined standards by an external body for the purposes of quality assurance and enhancement. In the context of HPE, accreditation is distinct from other forms of program evaluation or research. Accreditation can enhance health care outcomes because of its ability to influence and standardize the quality of training programs, continuously enhance curriculum to align with population needs, and improve learning environments. We describe ten fundamental and recurring elements of accreditation systems commonly found in HPE and provide an overview of five emerging developments in accreditation in the health professions based on the consensus findings. Conclusions Accreditation has taken on greater importance in contemporary HPE. These consensus findings provide frameworks of core elements of accreditation systems and both recurring and emerging design issues. HPE scholars, educators, and leaders can build on these frameworks to advance research, development, and operation of high-quality accreditation systems worldwide.